Problem-Based Learning Methods in Economics Subjects in Indonesian Educational Institutions: A Literature Review - Kanaga Retnam, Devaki; Azila Abdul Razak (International Business Education Journal, 2023)
The Problem-Based Learning Method (PBL) is known as the most innovative approach to develop students’ skills and abilities to solve real problems in the classroom and at work in the future. The highlights of this literature are aimed at reviewing the effectiveness of problem-based learning methods in economics subject for students, especially in Indonesia. Articles from 2016 to 2023 were obtained from three databases, Google Scholar, Research Gate, and Semantic Scholar. A total of 40 articles were selected based on four stages in the PRISMA Model, namely, identification, screening, eligibility, and inclusion. The findings showed that overall implementation of the PBL method had a more positive impact than conventional learning on economics students in Indonesia when teachers apply PBL models and PBL integration techniques in the global era of Society 5.0. Among the positive effects of this study were (1) students were able to improve economics learning outcomes, (2) students were able to improve critical thinking skills, (3) students could improve their performance in economics subject and (4) students could develop high order thinking skills (HOTS). The role of facilitator teachers was also emphasized in this study. Therefore, this study suggested that teachers and lecturers of economics should choose PBL techniques as one of the best solutions for implementing teaching and learning economics in the classroom in the global era of Society 5.0. This paper also highlighted the challenges faced by students and teachers in achieving the Minimum Profit Criteria set by the Ministry of Education Indonesia for further study.